Experience Reflection Modelling (ERM): a reflective medium encouraging dialogue between users and design students. Issue 1 (2nd January 2017) - Turhan, Senem; Doğan, Çağla
Abstract: Experience reflection modelling (ERM) as a design research method emerges out of participatory and generative research approaches. It includes tools and techniques that are put together strategically to enable the involvement of people in the early stages of the design process, connecting students and people by creating an effective medium for the knowledge transfer. In design education, ERM focuses on bridging the gap between the early stages of the design process and idea generation by providing students with techniques for revealing user knowledge, and encouraging them to combine design and user knowledge in the development of design solutions. This paper presents the ERM method, and explains its implications for an educational project and a field study. The intention in the study is to gain insights into ERM and to obtain students' reflections so as to develop it in such a way that it enriches student engagement. The study explores the motives and obstacles for each of the ERM phases; the factors affecting student engagement during their use of the method; its implications for idea generation; and the design students' intentions to use ERM in future design practice. The paper concludes with the suggestions and insights for ERM's further development.